Seasonal and Diurnal Variation of Black Carbon Aerosols over Delhi and their Interrelationship with PM2.5 and Meteorological Parameters - NC, Gupta; Tyagi, Charu; Sarma, Kiranmay; Pathak, Utkarsha (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Due to industrial, vehicular and residential emission in Delhi, concentration of Black carbon (BC) emitted is substantially high. Black carbon plays a major role in altering the earthâ€™s climate and leads to adverse human health. The current research estimates the concentration of Black Carbon, a light absorbing carbonaceous aerosol at four locations of Delhi during 2017. The intra-seasonal variation indicated that the average BC surface mass concentration was highest during winters around 26.27 Â± 3.28Î¼g/m3 followed by postmonsoon and pre-monsoon season. As per the diurnal variation, minimum BC concentration was found during the daytime between 12:00-17:00hrs due to enhancements in the MLH and increased convective activity. The BC mass concentration exhibit positive correlation with PM2.5. This study will add significant value to the current BC research literature. How to cite this article: Tyagi C, Gupta NC, Sarma K et al. Seasonal and Diurnal Variation of Black Carbon Aerosols over Delhi and their Interrelationship with PM2.5 and Meteorological Parameters. J Adv Res Alt Energ Env Eco 2018; 5(4): 29-32. DOI: https://doi.org/10.24321/2455.3093.201805